The The Prophetic and Servant Leadership Style of the Kindergarten Principal in Managing the Tunas Rimba Perhutani Cikawung Indramayu Kindergarten (TK) - Ningsih, Sri Puspa (Pergunu Jawa Barat, 2025)
The Principal in the Education Unit is a leader who has two positions, namely as a formal leader and school manager. In carrying out his duties, the principal has different strategies and methods according to his character, which is known as the leadership style. This study aims to analyze and describe the prophetic and servant leadership styles applied by the Head of Tunas Rimba Perhutani Cikawung-Indramayu Kindergarten, as well as how Islamic values are integrated in the management of these educational institutions. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation. The research informants consisted of the principal, teachers, administrative staff, representatives of the Taruna Rimba Perhutani Foundation, and representatives of student parents. Data were analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results showed that the Principal consistently applies a prophetic leadership style that includes the traits of Siddiq (honest), Amanah (responsible), Tabligh (communicative), and Fathanah (intelligent). In addition, the servant leadership style is also very prominent, realized through concern, empathy, and support for the needs of teachers, staff, and students. The integration of Islamic values such as justice, deliberation, and mutual cooperation (ta'awun) has led to the development of the school.